The Role of Prosodic Variation in Courtroom Discourse - محسن علي, سندس (Al-Adab Journal, 2018)
Firthian prosodic analysis asserts the integration of both phonematic units and prosodies in the sense that both constitute one whole of integration between system and structure. That integration is not simply a string of segments into a linear order rather is seen as a part of a larger relation. The context in which the prosodic features occur is intensively called for and this creates a system that cannot be applied or imposed upon other systems. Courtroom discourse shows spoken interaction that exhibits interesting prosodic features. Some prosodic features are more prominent than others, depending on the role of the speaker, the part of discourse, and the context. Polysystemicity is intended to show that each system carries its own rules and features that needless to be generalized to other systems. The use of each prosodic feature by each participant carries an aim which is different from other participant’s aims. Therefore what is significant in courtroom discourse is the proper employment of the prosodic features to achieve purposes by each participant on argumentation part which is the selected part of each trial in the study.